Dispersal in plants a population perspective - Cousens, Roger; Dytham, Calvin; Law, R. (Richard), 1950- (Oxford : Oxford University Press, 2008)
This advanced textbook explores the consequences of plant dispersal for population and community dynamics, spatial patterns, and evolution. It successfully integrates a rapidly expanding body of theoretical and empirical research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Plants -- Dispersal; Plant populations; Vegetation dynamics